Emission factors for polycyclic aromatic hydrocarbons from laboratory biomass-burning and their chemical transformations during aging in an oxidation flow reactor - Sengupta, Deep; Samburova, Vera; Bhattarai, Chiranjivi; Moosmüller, Hans; Khlystov, Andrey (The Science of the total environment, 2023)
Atmospheric polycyclic aromatic hydrocarbons (PAHs) can be emitted from different combustion sources including domestic biomass burning, internal combustion engines, and biomass burning (BB) in wild, prescribed, and agricultural fires. With climate warming and consequent global increases in frequency and severity of wildfires, BB is a dominant source of PAHs emitted into the atmosphere. In this study, six globally and regionally important and representative fuels (Alaskan peat, Moscow peat, Pskov peat, eucalyptus, Malaysian peat, and Malaysian agricultural peat) were burned under controlled conditions in the combustion chamber facility at the Desert Research Institute (DRI, Reno, NV, USA). Gas- and particle-phase BB emissions were aged in an oxidation flow reactor (OFR) to mimic five to sevendays of atmospheric aging. To sample gas- and particle-phase BB emissions, fresh and OFR-aged biomass-burning aerosols were collected on Teflon-impregnated glass fiber filters (TIGF) in tandem with XAD resin media for organic carbon speciation. The objectives of this study were to i) quantify the emission factors for 113 PAHs emitted from the combustion of the six selected fuels, ii) characterize the distribution of PAH compounds between gas and particle phases for these fuels, iii) identify the changes in PAHs during OFR-aging, and iv) evaluate toxicity potential with characterized compounds. We found that combustion emissions of gas-phase PAHs were more abundant (>80 % by mass) than particle-phase PAHs, for emissions from all combusted fuels. The mass fraction of substituted napthalenes in Moscow peat and Malaysian peat emissions were ∼70 % & 84 %, respectively, whereas in Eucalyptus the same fraction was <50 %, which indicates that these substituted compounds can be used as tracers for peat emissions. Mass concentrations of gas- and particle-phase PAHs were reduced by ∼70 % after OFR oxidation. However, the understanding of the fate of PAHs during OFR oxidation requires further investigations. Our results also indicate that the PAH toxicity of BB samples would be underestimated by 10–100 times if only the BaPeq for the 16 US EPA priority PAHs in the particle phase are included. [Display omitted] •Emissions of biomass burning PAHs are important because of their potential toxicity•Emissions of 113 PAHs and derivatives from combustion of six fuels were quantified•We used Gas Chromatography-Mass Spectrometry for analysis of PAHs and PAH derivatives•Analyzing only particle phase 16 EPA priority PAHs may greatly underestimate toxicity•Characterization of gas phase of PAHs is of the essence for PAH toxicity evaluation